Produção e composição bromatológica da forragem do capim-mombaça (Panicum maximum Jacq.), submetidos a diferentes fontes e doses de corretivo de acidez - Santana, Graciele Sarante; Magalhaes Bianchi, Pedro Paulo; Morita, Isabela Miyahira; Isepon, Olair Jose [UNESP]; Fernandes, Francisco Maximino [UNESP] (Universidade Estadual de Londrina (UEL), 2010)
The experiment was carried in protected (greenhouse) atmosphere, in University of Engineering, UN-ESP of Ilha Solteira-SP, with the objective of evaluating sources (limestone and calcium silicate slag) and doses (0,0 0,5 1,0 1,5 2,0 times the recommended dose) of corrective in the bromatolouic composition, tillering and production of dry matter of the grass mombaca (Nuncio? maximum Jacq.). The lineation was completely randomized design, with four repetitions. It was evaluated the tiller number, the production of dry matter, the gross protein, neutral detergent fiber (NDF) and acid detergent fiber (ADF). The corrective influenced the tillering in almost all of the countings. The limestone provided larger production of dry matter in the doses of 1,5 and 2,0 times the recommended dose. The bromatologic composition of the forage was not influenced by the corrective and doses.
Production and bromatologic composition of grass-mombaca (Panicum maximum Jacq.), submitted to different sources and doses of acidity corrective
Keywords: Limestone; calcium silicate slag; Panicum maximum Jacq.